Application of compatible dual‐echo arteriovenography in stroke: Preliminary observations. Issue 2 (21st May 2013) - Ty Bae, Kyongtae; Park, Sung‐Hong; Shim, Hackjoon; Moon, Chan‐Hong; Kim, Jung‐Hwan; Nemoto, Edwin M.
<x xml:space="preserve">Abstract</x> Compatible dual‐echo arteriovenography (CODEA) is a recent MRI technique for simultaneous acquisition of an MR angiogram (MRA) and MR venogram (MRV) with image quality comparable to conventional single‐echo acquisitions. The purpose of this study was to evaluate the utility of CODEA in imaging patients with chronic stroke and to test the utility of a new image representation technique ("enhanced maximum intensity projection [MIP]") based on tissue segmentation, intensity inversion, and vessel enhancement filtering) for MRV. Arterial and venous abnormalities associated with stroke were delineated on MRA and MRV acquired simultaneously with the CODEA technique. CODEA MRV displayed with the enhanced MIP technique facilitated the visualization of the overall venous structures in 3D. Reduced venous vascularity was detected in the regions of arterial occlusion compared to the contralateral normal brain regions. The CODEA technique along with the enhanced MIP technique may be valuable, particularly in clinical applications that require efficient MRA/MRV imaging because of limited scan time such as in acute stroke. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 152–156, 2013